Low serum 25-OH vitamin D levels are associated with increased D/P creatinine ratio in peritoneal dialysis patients - BARUTÇU ATAŞ, DİLEK; TUĞCU, MURAT; VELİOĞLU, ARZU; ARIKAN, İZZET HAKKI; AŞICIOĞLU, EBRU (My University, 2021)
Low 25-OH vitamin D levels have been linked to peritonitis and cardiovascular mortality in peritoneal dialysis (PD) patients. In this study we aimed to investigate the association of 25-OH vitamin D levels with peritoneal membrane characteristics in chronic PD patients. Consecutive 103 PD patients were enrolled in this retrospective study. Peritoneal dialysate to plasma (D/P) creatinine increase more than 0.1 with time were accepted as significant according Roc curve analysis. Patients with and without an increase in the D/P creatinine ratio of 0.1 were classified as Group 1 and Group 2, respectively. The relationship between baseline 25-OH vitamin D and peritoneal membrane characteristics were investigated. Mean age of the patients was 53.4±14.9 years and duration of PD was 72.1±50.3 months. There were thirty (29.1%) patients in Group 1. The duration of PD [73.5 (52.3-133.8) vs 49.0 (33.5-94.0) months, p:0.008]; hemoglobin [11.4 (10.4-12.2) vs. 10.2 (9.4-11.0) g/dL, p:0.001]and PTH [500.5 (254.5-748.3) vs 329.0 (205.0-549.5)ng/mL, p:0.047] levels were significantly higher in Group 1, whereas 25-OH vitamin D levels [5.0 (3.0-9.3) vs 7.8 (4.5-11.1)μg/L, p:0.027] and CRP [4.0 (3.0-7.2) vs. 8.0 (3.0-13.5)mg/L, p:0.028] were significantly lower. Multivariate analysis revealed duration of PD [Exp(B):1.012 (95%CI:1.001-1.022), p:0.028]; hemoglobin [Exp(B):1.756 (95%CI:1.199-2.571), p:0.004]; C-reactive protein (CRP) [Exp(B):0.882 (95%CI:0.789-0.985), p:0.026] and 25-OH vitamin D [Exp(B):0.853 (95%CI:0.754-0.965), p:0.012] were independent predictors of an increase in D/P creatinine ratio in PD patients. Increased D/P creatinine ratio was negatively correlated with 25-OH vitamin D level (r: -0.217, p:0.028). Lower levels of initial 25-OH vitamin D were associated with an increase in D/P creatinine ratio over-time.
Keywords: Inflammation; 25-OH vitamin D; chronic kidney disease; D/P creatinine ratio; peritoneal dialysis